2000
DOI: 10.1023/a:1026511420505
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reactive oxygen species (ROS) pose a serious threat to maternal and fetal health during pregnancy. However, there is little information on the oxidative damage caused by ROS and its protection during prenatal life. The present study highlights the status of various antioxidants in human placental and fetal tissues at different phases of gestation. The activity profile of scavenging enzymes, superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase as well as the concentrations of non-enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…This is consistent with the known developmental pattern of enzymatic antioxidant expression and activity and the availability of non-enzymatic antioxidants across gestation. The activity of the primary enzymatic antioxidants (catalase, superoxide dismutase and glutathione reductase) increases over pregnancy, while that of placental glutathione peroxidase remains unchanged (Qanungo & Mukherjea 2000). Conversely, serum or plasma levels of non-enzymatic antioxidants, including vitamin A (De Vriese et al 2001) and b-carotene (Oostenbrug et al 1998), decrease throughout pregnancy, while levels of a-tocopherol increase (Oostenbrug et al 1998, De Vriese et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the known developmental pattern of enzymatic antioxidant expression and activity and the availability of non-enzymatic antioxidants across gestation. The activity of the primary enzymatic antioxidants (catalase, superoxide dismutase and glutathione reductase) increases over pregnancy, while that of placental glutathione peroxidase remains unchanged (Qanungo & Mukherjea 2000). Conversely, serum or plasma levels of non-enzymatic antioxidants, including vitamin A (De Vriese et al 2001) and b-carotene (Oostenbrug et al 1998), decrease throughout pregnancy, while levels of a-tocopherol increase (Oostenbrug et al 1998, De Vriese et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a condition that favours oxidative stress; serum lipid peroxidation products are increased in normal pregnant women, particularly during the second trimester (Qanungo and Mukherjea 2000;Uotila et al 1991) while other cytoprotective enzymes and antioxidants are also elevated (Casanueva and Viteri 2003). Enhanced activities of superoxide dismutase were assayed in latent alveolar macrophages isolated from pregnant rats ± iron supplement on day 21.…”
Section: Discussionmentioning
confidence: 99%
“…Qanungo and colleagues found that SOD, catalase, GPx, and glutathione reductase activities increased with gestational age, as evidence of lipid peroxidation decreased in human placental and fetal tissues (5). Development of the antioxidant system during fetal life must also include redox signaling in the maintenance of pregnancy through uterine-placental-fetal interactions (6).…”
Section: Introductionmentioning
confidence: 99%